2019
DOI: 10.1111/gbb.12605
|View full text |Cite
|
Sign up to set email alerts
|

Lgl1 deficiency disrupts hippocampal development and impairs cognitive performance in mice

Abstract: Cellular polarity is crucial for brain development and morphogenesis. Lethal giant larvae 1 (Lgl1) plays a crucial role in the establishment of cell polarity from Drosophila to mammalian cells. Previous studies have found the importance of Lgl1 in the development of cerebellar, olfactory bulb, and cerebral cortex. However, the role of Lgl1 in hippocampal development during the embryonic stage and function in adult mice is still unknown. In our study, we created Lgl1‐deficient hippocampus mice by using Emx1‐Cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 81 publications
(168 reference statements)
0
6
0
Order By: Relevance
“…In 1967, Schneiderman and Gattiff reported on the rapid proliferation and invasion of cells observed in drosophila mutation, which was considered to be a form of malignant tumor [12]. Loss of Lethal giant larvae (D-Lgl) in Drosophila melanogaster leads to disruption of apical-basal polarity, defects in epithelial structure, and uncontrolled cell proliferation [7,13,14]. However, it remains unclear whether Lgl1 is involved in carcinogenesis in higher eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1967, Schneiderman and Gattiff reported on the rapid proliferation and invasion of cells observed in drosophila mutation, which was considered to be a form of malignant tumor [12]. Loss of Lethal giant larvae (D-Lgl) in Drosophila melanogaster leads to disruption of apical-basal polarity, defects in epithelial structure, and uncontrolled cell proliferation [7,13,14]. However, it remains unclear whether Lgl1 is involved in carcinogenesis in higher eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…of apical-basal polarity, defects in epithelial structure, and uncontrolled cell proliferation [7,13,14]. However, it remains unclear whether Lgl1 is involved in carcinogenesis in higher eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of a Drosophila l(2)gl cDNA in the sop1Δsop2Δ strain partially restored the Na + tolerance of the cells, indicating a novel function in cell homeostasis for this family of proteins extending from yeast to human (Larsson et al ., 1998). A recent study has shown that Lgl1 ‐deficient mice exhibited a disrupted hippocampal neuroepithelium, including increased cell proliferation, abnormal interkinetic nuclear migration, reduced differentiation, increased apoptosis, gradual disruption of adherens junctions, and abnormal neuronal migration (Zhang et al ., 2019). Lgl1 is also required for asymmetric cortical localization of all known basal determinants in mitotic neuroblasts (Peng et al ., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Lethal giant larvae 1 (Lgl1) was initially known as a tumor suppressor ( 24 ) and regulator of polarization processes in variety of cells ( 25 , 26 ). It has been confirmed that Lgl1 is enriched in developing axons, and upregulation of Lgl1, which has promoted the axonal growth during neuronal morphogenesis ( 27 ).…”
Section: Introductionmentioning
confidence: 99%